Terapi Massage Ekstremitas Bawah dengan Jasmine Aromatherapy dalam Menurunkan Skala Nyeri Persalinan - Haifa Wahyu; Liza Fitri Lina; Leni Rozani (Sistem Informasi, 2022)
Pain in labor is a natural process. If it is not handled properly it will cause other problems, namely, due to the knowledge and inexperience of the mother when facing childbirth so that hormone production increases and results in vasocontraction which causes blood flow to the mother will decrease. This study aims to measure the effectiveness of lower extremity massage with jasmine aromatherapy to reduce pain scale in latent phase in labor. The research method was pre-experimental design, the study used a one group pre-test-post-test design, which revealed a causal relationship by involving one group of subjects. The subject group was observed before the intervention, it was observed again after the intervention was carried out. The results of statistical analysis obtained p value: 0.001. The conclusion of this study is that lower extremity massage therapy with jasmine aromatherapy reduces pain scale in latent phase of labor.